Aluminium Pollution In Sediment Of Perai River, Penang - Azlan Shah, Siti Nuraqilah (Universiti Sains Malaysia, 2022)
For centuries, rivers provide various kinds of utilization components to humans. Development activities through discharge of effluents from different anthropogenic sources deteriorate the water quality and health aquatic ecosystem. The present study was conducted to determine the aluminium pollution in sediments of Perai river, Penang and its potential sources since there has been several news of irresponsible parties that dump their waste into the river. A total of 22 samples (11 samples for each month of February and April) is collected. Aluminium and other heavy metals were analyzed by using Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES) and X-ray diffraction (XRD). It is found that aluminium concentrations are higher during dry season than wet season due to the water dilution during rainy seasons. The results will be more concrete if there are samples collected at the potential sources. These results are very crucial to understand the aluminium pollution in Perai river based on heavy metals and the effects towards human health and environment.